Women economic empowerment via cash transfer and microcredit programs is enough to decrease intimate partner violence? Evidence from a systematic review - Tatiana Henriques Leite; Claudia Leite de Moraes; Emanuele Souza Marques; Rosangela Caetano; José Ueleres Braga; Michael Eduardo Reichenheim
Intimate partner violence (IPV) is a worldwide public health problem. Many proposals aiming to eliminate its occurrence include the empowerment of women through their socio-economic development. In this context, some studies suggested that microcredit programs (MP) and cash transfer programs (CTP) are initiatives that can also reduce the risk of IPV. Others pointed to an opposite effect. The objective of this study was to investigate the influence of women's economic empowerment in MP and CTP on the risk of physical, psychological and sexual violence through a systematic review. Papers/documents selection was conducted by two researchers according to the following criteria: published in English, Portuguese or Spanish; primary data; assessing the effect of MP or CTP on IPV; in heterosexual couples; on women beneficiaries of the intervention; using a comparator group eligible for an MP or CTP; and focusing on risk IPV as the outcomes. Our results showed that the impact of MP are mixed when it comes to physical and physical/sexual violence. Even so, the review suggests that the effect of MP on sexual violence is trivial or nonexistent. Regarding the impact of CTPs, the present study showed that the effects on physical, physical/sexual, psychological, and sexual violence were also heterogeneous. Women more empowered and with some autonomy could be at risk. Despite that, participation in the empowerment program should be encouraged for poor women and families. However, parallel interventions to lead with IPV should be addressed to the main actions to reduce the risk of increasing IPV prevalence in certain scenarios.